Radiation safety : management and programs - Domenech, Haydee (Springer, 2017)
This book discusses important fundamentals of radiation safety with specific details on dose units, calculations, measuring, and biological effects of ionizing radiation. The author covers different exposure situations and their requirements, and relevant legislation and regulations governing radiation safety. The book also examines radioactive waste management, the transport of radioactive materials, emergency planning and preparedness and various examples of radiation protection programs for industrial, medical, and academic applications. .
Keywords: Radiation -- Safety measures.; Ionizing radiation -- Safety measures.; elektronické knihy; electronic books